Multifunctional Hybrid Interfacial Layers for High‐Performance Inverted Perovskite Solar Cells - Niu, Benfang; Liu, Haoran; Huang, Yanchun; Gu, Emely; Yan, Minxing; Shen, Ziqiu; Yan, Kangrong; Yan, Buyi; Yao, Jizhong; Fang, Yanjun; Chen, Hongzheng; Li, Chang‐Zhi (Advanced materials (Weinheim), 2023)
Challenges remain hindering the performance and stability of inverted perovskite solar cells (PSCs), particularly for the nonstable interface between lead halide perovskite and charge extraction metal oxide layer. Herein, a simple yet scalable interfacial strategy to facilitate the assemble of high‐performance inverted PSCs and scale‐up modules is reported. The hybrid interfacial layer containing self‐assembly triphenylamine and conjugated poly(arylamine) simultaneously improves the chemical stability, charge extraction, and energy level alignment of hole‐selective interface, meanwhile promoting perovskite crystallization. Consequently, the correspondent inverted PSCs and modules achieve remarkable power conversion efficiencies (PCEs) of 24.5% and 20.7% (aperture area of 19.4 cm2), respectively. The PSCs maintain over 80% of its initial efficiency under one‐sun equivalent illumination of 1200 h. This strategy is also effective to perovskite with various bandgaps, demonstrating the highest PCE of 19.6% for the 1.76‐eV bandgap PSCs. Overall, this work provides a simple yet scalable interfacial strategy for obtaining state‐of‐the‐art inverted PSCs and modules. A simple yet scalable interfacial layer consisting of self‐assembled molecule and conjugated polymer facilitates resolving bilateral surface issues between charge‐selective metal oxide and perovskite, successfully leading to high‐performance inverted perovskite solar cells and modules.